Qualitative inquiry and research design : choosing among five approaches - Creswell, John W.; Creswell, John W. (Los Angeles : SAGE Publications, 2013)
The text provides a wonderful introduction, using accessible language, to theories and practices related to the design and conduct of qualitative inquiry. Moreover, it remains a good first resource for students who want to pursue qualitative inquiry. The book explores the philosophical underpinnings, history and key elements of each of the five qualitative inquiry traditions: narrative research, phenomenal, grounded theory, ethnography and case study.
Previous ed. cataloged as: Qualitative inquiry & research design. c2007.
Includes bibliographical references (p. 417-434) and indexes.
opc 24/07/13
Loans
Keywords: Social sciences